Review paperPercutaneous balloon aortic valvuloplasty in different age groups - Olasińska-Wiśniewska, Anna; Trojnarska, Olga; Grygier, Marek; Lesiak, Maciej; Grajek, Stefan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Aortic stenosis is a congenital or acquired reduction in the area of the aortic valve, resulting in obstruction of the blood flow from the left ventricle to the aorta. Aortic stenosis accounts for 2-5% of all congenital heart defects and is a potentially life-threatening disorder. In adults aortic stenosis represents 34% of all valvular heart diseases. Degenerative etiology is present in 80% of cases. Patients with mild aortic stenosis are usually asymptomatic. Symptoms of the disease occur along with the disappearance of effective compensatory mechanisms. These are symptoms of low cardiac output syndrome manifested as fainting, dizziness, ischemic pains, exercise intolerance, arrhythmias with the risk of sudden cardiac death, and heart failure. As soon as the symptoms occur the prognosis significantly worsens, which is associated with a high risk of death. Percutaneous aortic valvuloplasty is a palliative method of treatment of aortic stenosis. The aim of the procedure is to relieve left ventricular outflow tract obstruction, thereby improving cardiac output. The etiology, course of the aortic stenosis and treatment methods, including invasive procedures, vary depending on the patients’ age. The purpose of this paper is to present the characteristics of the aortic valve disease and the strategy of aortic balloon valvuloplasty in different age groups.